Cytotoxic effect of 2,6-bis(4-hydroxy-3-methoxybenzylidene) cyclohexanone (BHMC) and curcumin on human liver cancer cells, HepG2 - Syed Alwi, Sharifah Sakinah; Zahari, Syazwan; Haron, Aminah Suhaila; Alexander, Henna Roshini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Curcumin is an active constituent derived from turmeric with a variety of pharmacological activities. It suppressed cell proliferation and induced apoptosis in several cancer cell lines. However, due to its poor bio-availability, derivative analogue of curcumin has been synthesized to enhance the drug-like effects. BHMC was synthesized by removing β-diketone moiety from curcumin structure and modify it into conjugated double bonds. It has been proved to exhibit stronger anticancer effects with improved bioavailability compared to curcumin. Objective: This study aims to investigate the toxicity effect of BHMC and curcumin on human liver cancer, HepG2 and non-cancer mouse fibroblast, 3T3. Methods: Both cell lines were purchased from ATCC and cultured in supplemented DMEM. Cell viability was determined via MTT assay and confirmed with trypan blue assay. Morphology hallmarks of apoptosis of both treated cells were analyzed using inverted microscope at 40X magnifications. Results: BHMC and curcumin were very potent towards HepG2 and normal 3T3. These data were further confirmed with trypan blue assay which showed that both compounds significantly reduced the percentage of HepG2 and 3T3 cells viability. Both treated cells also displayed all the morphology hallmarks of apoptosis upon treatment. Conclusion: BHMC has a greater cytotoxicity effect on HepG2 compared to curcumin despite its non-selective cytotoxicity effect on non-cancer 3T3.